COVID-19 infection manifesting as a severe gastroparesis flare: A case report. Issue 14 (9th April 2021) - Song, Jun; Bhuta, Rajiv; Baig, Kamal; Parkman, Henry P.; Malik, Zubair
Abstract: Rationale: Coronavirus disease 2019 (COVID-19) is a disease caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which commonly presents with symptoms including fever, cough, and dyspnea. More recently, however, some patients have tested positive for COVID-19 after developing gastrointestinal (GI) symptoms either solely or in conjunction with respiratory symptoms. This may be due to SARS-CoV-2 infection of the GI tract. In patients with chronic GI illnesses, COVID-19 may initially present as a flare of their underlying GI conditions as viruses have historically been implicated in exacerbations of GI disorders, including gastroparesis. Patient concerns: We report a case of a 37-year-old female with a history of diabetic gastroparesis who presented to the Emergency Department (ED) with nausea and vomiting similar to her gastroparesis flares. Diagnoses: Her symptoms in the ED failed to improve with fluids and anti-emetic medications. After developing a fever, she was tested and found to be positive for COVID-19. Interventions: She was started on antibiotic, steroid, and antiviral medications. Outcomes: Her symptoms improved, her fever defervesced on day 4 of hospitalization, and she was discharged on day 5 of hospitalization. The patient reported symptom improvement at a follow-up outpatient gastroenterology visit 2 months after hospitalization. Lessons: To the best of our knowledge, at the present time, this is the first report of a patient with COVID-19 presenting with signs and symptoms of a gastroparesis flare. This case illustrates that COVID-19 may present in an exacerbation of symptoms of an underlying disorder, such as a severe gastroparesis flare, in a patient with underlying gastroparesis. Initial presentation of these patients manifesting as a flare of their chronic GI disease, more severe than usual, should prompt an index of suspicion for COVID-19.